2018
DOI: 10.9734/ajeba/2018/44493
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality and Customer Satisfaction of Electricity Distribution Company: A Study of Olumo Business Hub, Abeokuta, Ogun State

Abstract: This study examines the relationship between service quality and customer satisfaction in Ibadan Electricity Distribution Company. To achieve this, IBEDC customers residing in Ogun State were sampled to seek their opinion on their level of satisfaction with IBEDC's services. Survey research was employed which involved the distribution of questionnaires to customers. The questionnaire sought information based on the five SERVQUAL dimension of reliability, empathy, responsiveness, tangibles and assurance which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…The states of residence of the respondents are a major factor in the DISCOs that supply them. For example, IBEDC supplies Osun and Ogun among other states (Olayinka et al, 2018). Lagos State is supplied by IKEDC and EKEDC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The states of residence of the respondents are a major factor in the DISCOs that supply them. For example, IBEDC supplies Osun and Ogun among other states (Olayinka et al, 2018). Lagos State is supplied by IKEDC and EKEDC.…”
Section: Resultsmentioning
confidence: 99%
“…Investigating electricity consumers’ satisfaction in Nigeria had been carried out in recent past by various authors. In the work of Olayinka et al (2018), he examines the relationship between service quality and customer satisfaction in Ibadan Electricity Distribution Company (IBEDC). The author specifically focused on the residence of Ogun State.…”
Section: Introductionmentioning
confidence: 99%
“…This study uses a research methodology, as shown in Figure 1. power company using exploratory factor analysis (EFA), and research of [11] in the Nigerian power company, three dimensions of electricity service quality are taken as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Reliability is to provide consistent service as expected by customers [11]. Reliability results in customer retention when a service provider can supply services accurately and continuously by client expectations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation